Evolutionary game model of migraine based on the human brain hypersensitivity - Han, Dong-Gyun (Frontiers in Neurology, 2023)
Based on all studies published until 2020, the prevalence of migraine is approximately 14% worldwide, though varied regionally. Despite one of the most disabling diseases, migraine still exists through natural selection and is prevalent up to date. This brings out the question of what evolutionary advantages have led to migraine survival. The ultimate answer to this question should be found in evolution; however, there is no clear explanation yet. Notably, all the genes that cause migraine make migraineur’s sensory organs and cortices hypersensitive. The brain, in a state of hypersensitivity, could recognize external threats easily. The game theory is a useful tool for explaining evolution in terms of genes. Just as the Hawk‒Dove game, which shows two strategies (aggressive and passive) and four fitness values, an evolutionary game between a migraineur and a non-migraineur, which shows two phenotypes (more sensitive and less sensitive) and four fitness values, can be played if a migraineur quickly recognizes a predator and informs a non-migraineur of its appearance and later, in return, the non-migraineur helps the migraineur escape danger. In this study, I aimed to explore the evolutionary mechanics of migraine that can be modelled. Furthermore, I tried to define why the human brain hypersensitivity is a prerequisite for developing this evolutionary game model.